Some theoretical considerations in applying cost-benefit analysis to Black education in South Africa - Hosking, Stephen Gerald (Rhodes University, Faculty of Commerce, Department of Economics, 1983)
From introduction: In this thesis some of the economic theory underlying the application of cost-benefit analysis to education is considered with the view to discussing its relevance to the field of educational provision for Black people in South Africa. The fact that educational facilities available to Blacks are so vastly inferior to those of the Whites has given rise to virtual consensus that more has to be provided for the Black population. The economic implications of education are frequently cited to support this viewpoint. Using (a ) the theoretical bases established in chapters 1 and 2, (b) the review of the rate of return to education studies in chapter 3 and (c) the broader socio-economic considerations introduced in chapter 4, it is concluded that this viewpoint is not necessarily well founded in South Africa and that the potential for greater use of the techniques described, is far from exhausted.
Keywords: Cost effectiveness; Black people -- Education -- South Africa -- Economic aspects; Education -- Economic aspects -- South Africa; Education -- Finance -- South Africa